Evaluating the effectiveness of kakawate (gliricidia sepium) leaf as an alternative insect repellent - Villa, Christine L. (San Miguel, Iriga City: University of Saint Anthony, 2024)
Evaluating the effectiveness of kakawate (gliricidia sepium) leaf as an alternative insect repellent.
Includes bibliographical references.
English